Bleak but Not Hopeless: Higher Education in Lebanon in Times of Multiple Crises - Schmäling, Benjamin (International Higher Education, 2024)
The economic and political situation in Lebanon has been worsening since 2019, with wide-ranging repercussions on the society in general, as well as on the higher education system. Despite this, Lebanese universities have shown remarkable resilience, engaging in partnerships and programs that support their own institutional survival and developing initiatives to address economic challenges. Such resilience, however, should not be taken for granted and requires active support to be maintained.